Perception of Riau Muslim Entrepreneurs on the Merger of Islamic Commercial Banking into Indonesian Islamic Bank - Marabona Munthe; Mohd Winario (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2021)
The purpose of this study is to further examine the perceptions of Muslim entrepreneurs in Riau towards the merger of a Islamic Commercial Banking to become an Indonesian Islamic bank. The method used is a qualitative method generated from a questionnaire filled out by Muslim entrepreneurs in Riau Province, explaining the perception of Riau Muslims about the merger of Islamic banks under BUMN. The results of this study indicate that the perceptions of Muslim entrepreneurs in Riau towards the joining of Islamic banks as BUMN, in this case Bank Syariah Mandiri, BNI Syariah and BRI syariah to become Bank Syariah Indonesia which is abbreviated as BSI in general have different perceptions, there are still many who disagree. by joining the Islamic Bank under the BUMN. Entrepreneurs are also not too sure about the joining of the Islamic Bank to become the icon and direction of the World Islamic Bank, they think that the joining of the Bank is influenced by political elements among the political elite. However, Muslim entrepreneurs in Riau on average will still become customers of Indonesian Islamic Bank, because apart from being a Islamic bank, there is no better choice than other banks. Tujuan penelitian ini adalah untuk mengkaji lebih jauh persepsi pengusaha muslim Riau terhadap penggabungan Bank Syariah BUMN menjadi bank syariah Indonesia. Metode yang digunakan adalah kualitatif yang dihasilkan dari kuisioner yang diisi oleh para pengusaha muslim yang ada di Provinsi Riau, menjelaskan mengenai persepsi muslim riau terhadap mergernya bank syariah di bawah BUMN. Hasil penelitian ini menunjukan bahwa persepsi pengusaha muslim riau terhadap bergabungnya bank syariah di bawah BUMN dalam hal ini Bank Syariah Mandiri, BNI Syariah dan BRI syariah menjadi Bank Syariah Indonesia yang disingkat menjadi BSI secara umum memiliki persepsi yang berbeda-beda, masih banyak yang tidak setuju dengan begabungnya Bank Syariah BUMN tersebut. Pengusaha juga tidak terlalu yakin dengan bergabungnya Bank Syariah tersebut menjadi icon dan kiblat Bank Syariah dunia, mereka menganggap bergabungnya Bank banyak dipengaruhi oleh unsur politis dikalangan elit politik. Namun pengusaha muslim Riau rata-rata tetap akan menjadi Nasabah Bank Syariah Indonesia, karena selain merupakan bank syariah, dan tidak ada pilihan lain yang lebih baik dari bank lain. Kata Kunci: Persepsi, Pengusaha Muslim, Merger, Bank Syariah.